Isolation, probiotic properties, and whole-genome analysis of P. acidilactici M22 from feline milk: a promising candidate for simulated pet milk formulations - Gong, Xinyu; Wang, Xue; Chen, Lu; Wang, Zhengping; Han, Jun; Wen, Min (Frontiers in Microbiology, 2025)
Breast milk constitutes a rich source of bacteria essential for the establishment and modulation of neonatal microbiota, playing a critical role in neonatal health. However, probiotic strains are rarely identified in feline milk. This study successfully isolated Pediococcus acidilactici M22 from feline milk and comprehensively evaluated its potential as a probiotic candidate for simulated pet milk formulations. Strain M22 demonstrated high tolerance to acidic conditions (survival rates of 59.93%, 94.15%, and 95.06% at pH 2.5, 3.0, and 4.0, respectively) and bile salts (survival rates of 96.01%, 96.35%, and 84.38% at 0.1%, 0.2%, and 0.3% concentrations, respectively). Furthermore, M22 exhibited strong adhesion (69.23%) to Caco-2 intestinal epithelial cells, Strong suppression of Escherichia coli O157, Staphylococcus aureus, and Salmonella Typhimurium SL1344, a negative hemolytic phenotype, and sensitivity to antibiotics (e.g., gentamicin). Conversely, tests on C57BL/6 mice, which were randomly split into four groups, showed that giving M22 orally did not harm the mice, raised serum SOD levels, and lowered MDA and BUN levels. These findings indicate that oral administration of M22 significantly enhances the in vivo antioxidant capacity of mice. Further more, genomic analysis revealed 1,960 coding sequences, two CRISPR loci, five genomic islands, and two prophage regions. Collectively, these findings indicate that P. acidilactici M22 possesses significant potential as a probiotic to improve the health and well-being of pets.